43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-490
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Slope Limiters on Irregular Grids

Abstract: This paper examines the behavior of flux and slope limiters on non-uniform grids in multiple dimensions. Many slope limiters in standard use do not preserve linear solutions on irregular grids impacting both accuracy and convergence. We rewrite some well-known limiters to highlight their underlying symmetry, and use this form to examine the properties of both traditional and novel limiter formulations on non-uniform meshes. A consistent method of handling stretched meshes is developed which is both linearity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 9 publications
0
115
0
Order By: Relevance
“…Many slope limiters have been derived for regular space discretizations (LeVeque, 2002), but very few are available for irregular meshes (Berger et al, 2005;Zeng, 2013). StreamFlow implements the slope limiter developed by Zeng (2013),…”
Section: Stream Energy-balance Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many slope limiters have been derived for regular space discretizations (LeVeque, 2002), but very few are available for irregular meshes (Berger et al, 2005;Zeng, 2013). StreamFlow implements the slope limiter developed by Zeng (2013),…”
Section: Stream Energy-balance Computationmentioning
confidence: 99%
“…Equation (16) is discretized over each stream reach using an explicit upwind finite volume scheme with second-order precision in space and first-order precision in time (Berger et al, 2005):…”
Section: Stream Energy-balance Computationmentioning
confidence: 99%
“…However, Berger et al [65] recently showed improved results using a gradient-based approach. This method should be evaluated.…”
Section: 1)mentioning
confidence: 99%
“…The limiter is applied to the gradient term, ∂w ∂x , in (2.86). The use of slope limiters is discussed in Toro [53], Berger et al [65], and Barth [66].…”
Section: Second-order Extensionmentioning
confidence: 99%
“…The initial problem setup is illustrated in Figure 5.1. that we could make to improve the solution, such as implementing a monotonic slope limiter [3] or tuning of the qquad and qlin artificial viscosity coefficients.…”
Section: The Sod Shock Tubementioning
confidence: 99%